Pseudomonas aeruginosa post‐translational responses to elevated c‐di‐GMP levels. Issue 5 (11th April 2022) - Bense, Sarina; Witte, Julius; Preuße, Matthias; Koska, Michal; Pezoldt, Lorena; Dröge, Astrid; Hartmann, Oliver; Müsken, Mathias; Schulze, Julia; Fiebig, Timm; Bähre, Heike; Felgner, Sebastian; et al.
Abstract: C‐di‐GMP signaling can directly influence bacterial behavior by affecting the functionality of c‐di‐GMP‐binding proteins. In addition, c‐di‐GMP can exert a global effect on gene transcription or translation, for example, via riboswitches or by binding to transcription factors. In this study, we investigated the effects of changes in intracellular c‐di‐GMP levels on gene expression and protein production in the opportunistic pathogen Pseudomonas aeruginosa . We induced c‐di‐GMP production via an ectopically introduced diguanylate cyclase and recorded the transcriptional, translational as well as proteomic profile of the cells. We demonstrate that rising levels of c‐di‐GMP under growth conditions otherwise characterized by low c‐di‐GMP levels caused a switch to a non‐motile, auto‐aggregative P. aeruginosa phenotype. This phenotypic switch became apparent before any c‐di‐GMP‐dependent role on transcription, translation, or protein abundance was observed. Our results suggest that rising global c‐di‐GMP pools first affects the motility phenotype of P. aeruginosa by altering protein functionality and only then global gene transcription. Abstract : The constitutively active diguanylate cyclase PleD* of Caulobacter crescentus was used to generate a Pseudomonas aeruginosa strain with elevated c‐di‐GMP levels in exponential growth phase. The cellular consequences were profiled on a global scale by RNA‐seq, ribosome profiling, proteome and phenotypic analyses. Our data reveal, that phenotypic adaption (impaired motility, auto‐aggregative growth) occurs rapidly and before any c‐di‐GMP‐dependent role on transcription, translation, or protein abundance could be observed.